Mechanical and structural optimization of flax fiber reinforced composites through controlled gamma irradiation - Madhu P; Sharath B N; Srinath M S; Pradeep S; Femiana Gapsari; Ari Wahjudi; Sanjay M R; Suchart Siengchin (iScience, 2025)
Summary: This study explores the effects of gamma irradiation on the mechanical and water absorption properties of flax fabric–reinforced epoxy composites for aerospace applications. Composites were fabricated using a manual lay-up technique and subjected to irradiation doses of 0, 100, 300, and 500 k rad. The laminate that was irradiated at 300 k rad (L3) had the best tensile, flexural, impact, and interlaminar shear strengths, and it also absorbed the least amount of water. Scanning electron microscopy showed better interfacial bonding and fewer defects, which proved that L3 had better structural integrity and durability. These results highlight the potential of flax-epoxy composites as environmentally sustainable, durable, and lightweight materials for aerospace components. Their ability to withstand extreme conditions makes them suitable for structural panels, protective enclosures, and insulation layers in space applications. Further studies can refine these composites by exploring hybrid reinforcements and advanced fabrication methods for improved performance under diverse environmental conditions.